Inhibition of signal peptidase complex expression affects the development and survival of Schistosoma japonicum - Yang, Wen-Bin; Luo, Fang; Zhang, Wei; Sun, Cheng-Song; Tan, Cong; Zhou, An; Hu, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Background Schistosomiasis, the second most neglected tropical disease defined by the WHO, is a significant zoonotic parasitic disease infecting approximately 250 million people globally. This debilitating disease has seriously threatened public health, while only one drug, praziquantel, is used to control it. Because of this, it highlights the significance of identifying more satisfactory target genes for drug development. Protein translocation into the endoplasmic reticulum (ER) is vital to the subsequent localization of secretory and transmembrane proteins. The signal peptidase complex (SPC) is an essential component of the translocation machinery and functions to cleave the signal peptide sequence (SP) of secretory and membrane proteins entering the ER. Inhibiting the expression of SPC can lead to the abolishment or weaker cleavage of the signal peptide, and the accumulation of uncleaved protein in the ER would affect the survival of organisms. Despite the evident importance of SPC, in vivo studies exploring its function have yet to be reported in S. japonicum. Methods The S. japonicum SPC consists of four proteins: SPC12, SPC18, SPC22 and SPC25. RNA interference was used to investigate the impact of SPC components on schistosome growth and development in vivo. qPCR and in situ hybridization were applied to localize the SPC25 expression. Mayer’s carmalum and Fast Blue B staining were used to observe morphological changes in the reproductive organs of dsRNA-treated worms. The effect of inhibitor treatment on the worm’s viability and pairing was also examined in vitro. Results Our results showed that RNAi-SPC delayed the worm's normal development and was even lethal for schistosomula in vivo. Among them, the expression of SPC25 was significantly higher in the developmental stages of the reproductive organs in schistosomes. Moreover, SPC25 possessed high expression in the worm tegument, testes of male worms and the ovaries and vitellarium of female worms. The SPC25 knockdown led to the degeneration of reproductive organs, such as the ovaries and vitellarium of female worms. The SPC25 exhaustion also reduced egg production while reducing the pathological damage of the eggs to the host. Additionally, the SPC-related inhibitor AEBSF or suppressing the expression of SPC25 also impacted cultured worms’ pairing and viability in vitro. Conclusions These data demonstrate that SPC is necessary to maintain the development and reproduction of S. japonicum. This research provides a promising anti-schistosomiasis drug target and discovers a new perspective on preventing worm fecundity and maturation.